Hubungan Pengetahuan dengan Kejadian Hipertensi di Puskesmas Jekan Raya Kota Palangka Raya Provinsi Kalimantan Tengah: The Relationship of Knowledge With the Event of Hypertension at Jekan Raya Puskesmas, Palangka Raya City Central Kalimantan Province - Egi Wiranto; Lensi Natalia Tambunan; Eva Prilelli Baringbing (Jurnal Surya Medika (JSM), 2023)
Hypertension or high blood pressure is an increase in blood pressure in the arteries. Risk of Hypertension if not treated immediately, can lead to the emergence of serious diseases that can threaten the life of the patient. Knowledge is a very important domain in shaping a person's behavior, lack of public knowledge will affect the occurrence of hypertension. The purpose of this study was to determine the relationship between knowledge and events in the working area of ​​the UPT Puskesmas Jekan Raya. The design of this research is an analytic survey with a cross sectional approach, the population in this study are hypertension sufferers in the working area of ​​the UPT Puskesmas Jekan Raya aged 15-70 years and over a number of 189 people using accidental sampling and taken from January to July 2022. The results of this study indicate that there is a relationship between knowledge and the incidence of hypertension at the Jekan Raya Public Health Center, Central Kalimantan Province, Palangka Raya City (p value 0.000 <a = 0.05. Conclusion: The community is expected to not only receive education from health workers, but also not to neglect the effects of hypertension. can cause complications. It is also hoped that the community always carries out health checks at the nearest health center.